Multi-dimensional charge transport in supramolecular helical foldamer assemblies - Méndez-Ardoy, Alejandro (Royal Society of Chemistry, 2017)

(untitled) (Chem Sci)
Aromatic foldamers are bioinspired architectures whose potential use in materials remains largely unexplored. Here we report our investigation of vertical and horizontal charge transport over long distances in helical oligo-quinolinecarboxamide foldamers organized as single monolayers on Au or SiO(2). Conductive atomic force microscopy showed that vertical conductivity is efficient and that it displays a low attenuation with foldamer length (0.06 Å(–1)). In contrast, horizontal charge transport is found to be negligible, demonstrating the strong anisotropy of foldamer monolayers. Kinetic Monte Carlo calculations were used to probe the mechanism of charge transport in these helical molecules and revealed the presence of intramolecular through-space charge transfer integrals approaching those found in pentacene and rubrene crystals, in line with experimental results. Kinetic Monte Carlo simulations of charge hopping along the foldamer chain evidence the strong contribution of multiple 1D and 3D pathways in these architectures and their dependence on conformational order. These findings show that helical foldamer architectures may provide a route for achieving charge transport over long distance by combining multiple charge transport pathways.